2021
DOI: 10.1002/1348-9585.12257
|View full text |Cite
|
Sign up to set email alerts
|

Exposure characterization and risk assessment of ultrafine particles from the blast furnace process in a steelmaking plant

Abstract: Objectives This study aimed to clarify the exposure characteristics and risks of ultrafine particles from the blast furnace process and to provide a reasonable control strategy for protecting the health of workers. Methods The blast furnace location of a steelmaking plant was selected as a typical investigation site. A membrane‐based sampling system was used to collect ultrafine particles to analyze their morphology and elemental compositions. A real‐time system was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
(43 reference statements)
2
4
0
Order By: Relevance
“…Size distribution analysis revealed that the predominant size of the submicron particles in the workshop air during the activity period ranged between 30 and 200 nm. The size distribution of the submicron particles during the activity period was bimodal (Figure 3C), which is in agreement with our previous study that reported a bimodal size distribution of submicron particles in a steelmaking plant (Gao et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Size distribution analysis revealed that the predominant size of the submicron particles in the workshop air during the activity period ranged between 30 and 200 nm. The size distribution of the submicron particles during the activity period was bimodal (Figure 3C), which is in agreement with our previous study that reported a bimodal size distribution of submicron particles in a steelmaking plant (Gao et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…The variation in the size of personal NC during working time was bimodal with values of 40 and 60 nm (Figure 4b), which suggested the primary size of particles and the agglomerate state or aerosol nucleation. This is consistent with a previously reported bimodal size distribution of submicron particles in a steel-making plant [51].…”
Section: Discussionsupporting
confidence: 93%
“…For the worker selected in this study, the ADDs in the olfactory area and brain were 2.19 × 10 −7 mg/kg•d −1 and 4.35 × 10 −8 mg/kg•d −1 , respectively. Previous studies have reported on the effects of submicron particles in the brain [51,52]. Submicron particles that accumulate in the brain not only translocate and directly damage neural tissue but also affect autonomic function [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…The conformance probability is as follow using equation (7), with 𝑚 → ∞, 𝑛 = 𝑇 𝑈 , and note that 𝜑(−∞) = 0:…”
Section: *Single Upper Tolerance Limitmentioning
confidence: 99%
“…The pig iron temperature, circular pressure, and hot wind temperature are the most important indicators of blast furnace production and hazard; so by only predicting the multivariate risk of those parameters can approximately control blast furnace process. Nowdays there are many ways for blast furnace risk assessment research, we can cite failure modes and effects analysis (FMEA) [17], ultrafine particle risk assessment in the blast furnace production process [7], hazardous amounts of cement based solidification process are produced when fly ash and blast furnace slag from municipal solid waste incinerators are combined [12], forecast of blast furnace gas production using data driven and mechanism techniques [11] and [16] and modeling and identifying metallurgical systems using multivariate statistical control and data mining techniques [7,8,10,19].…”
Section: Introductionmentioning
confidence: 99%